2009
DOI: 10.1038/nrg2537
|View full text |Cite
|
Sign up to set email alerts
|

Mapping complex disease traits with global gene expression

Abstract: Preface Variation in gene expression is an important mechanism underlying susceptibility to complex disease. The simultaneous genome-wide assay of gene expression and genetic variation allows the mapping of the genetic factors that underpin individual differences in quantitative levels of expression (expression Quantitative Trait Loci, eQTL). The availability of systematically generated eQTL information may provide immediate insight into a biological base for disease associations identified through genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
650
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(665 citation statements)
references
References 106 publications
(166 reference statements)
10
650
1
4
Order By: Relevance
“…Variants that change the amino acid sequence of proteins are more likely to affect phenotype than random sites in the genome, and this is used in the Bayes RC method described above. However, evidence is mounting that the majority of mutations that give rise to variation in complex traits reside in regulatory elements that alter gene expression [30][31][32] (reviewed by Pai et al [33]). …”
Section: Discussionmentioning
confidence: 99%
“…Variants that change the amino acid sequence of proteins are more likely to affect phenotype than random sites in the genome, and this is used in the Bayes RC method described above. However, evidence is mounting that the majority of mutations that give rise to variation in complex traits reside in regulatory elements that alter gene expression [30][31][32] (reviewed by Pai et al [33]). …”
Section: Discussionmentioning
confidence: 99%
“…73 The association between nucleotide variants in a regulatory element of LCT gene and the lactase persistence phenotype in European population, identified about 10 years ago, 74 is one of the first -and perhaps better-knowndemonstration of this hypothesis. Since then, GWAS have unequivocally shown that SNPs affect gene expression.…”
Section: Rna-seq In Human Complex Diseases V Costa Et Almentioning
confidence: 99%
“…Subtle effects of these SNPs on gene expression could be a functional mechanism by which they confer risk for development of schizophrenia. 10,11 Recently, it has been shown that true GWAS hits are enriched for expression QTLs (eQTLs). [11][12][13][14] Therefore, variations influencing gene expression are more likely to be contributing to the phenotype.…”
Section: Introductionmentioning
confidence: 99%